2021
DOI: 10.1186/s13567-021-00973-3
|View full text |Cite
|
Sign up to set email alerts
|

Ferulic acid inhibits LPS-induced apoptosis in bovine mammary epithelial cells by regulating the NF-κB and Nrf2 signalling pathways to restore mitochondrial dynamics and ROS generation

Abstract: In bovine mammary epithelial cells (BMECs), a cascade of inflammatory reactions induced by lipopolysaccharide (LPS) has been shown to result in cell injury and apoptosis. The present study aims to reveal the protective effect of ferulic acid (FA) on LPS-induced BMEC apoptosis and explore its potential molecular mechanisms. First, we showed that FA had low cytotoxicity to BMECs and significantly decreased cell apoptosis and the proinflammatory response induced by LPS. Next, FA blocked LPS-induced oxidative stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 47 publications
2
19
0
Order By: Relevance
“…Current studies have proved the importance of excessive ROS in inducing various cell apoptosis by the damage of lipids, proteins, and DNA in cells [ 53 , 54 ]. Our study demonstrated that the increase of ROS participated in LPS-induced apoptosis of BMECs, which was consistent with a previous study [ 46 , 55 ]. Moreover, excessive generation of ROS and the deficiency of antioxidants can result in the occurrence of oxidative stress which contributes to cell inflammation by inducing several signal molecules [ 38 ].…”
Section: Discussionsupporting
confidence: 94%
“…Current studies have proved the importance of excessive ROS in inducing various cell apoptosis by the damage of lipids, proteins, and DNA in cells [ 53 , 54 ]. Our study demonstrated that the increase of ROS participated in LPS-induced apoptosis of BMECs, which was consistent with a previous study [ 46 , 55 ]. Moreover, excessive generation of ROS and the deficiency of antioxidants can result in the occurrence of oxidative stress which contributes to cell inflammation by inducing several signal molecules [ 38 ].…”
Section: Discussionsupporting
confidence: 94%
“…In the study, LPS stimulated RAW264.7 cells to produce ROS at 3 h. DE reduced ROS production at 3 h of LPS stimulation. The nuclear transcription factor Nrf2 has been reported to play an important regulatory role in ROS production, and Nrf2 activity is inhibited at the very beginning of LPS stimulation of cells before it is activated ( Liu et al, 2021 ). ROS production is likely to be regulated by Nrf2, with early LPS stimulation resulting in decreased Nrf2 production and increased ROS production, and as time passes, Nrf2 production rises and ROS production declines.…”
Section: Discussionmentioning
confidence: 99%
“…In mastitis, the release of ROS is key to the inflammatory response [ 45 ]. On the one hand, ROS plays an important role in inflammation, apoptosis, and cell growth [ 46 , 47 ]. On the other hand, ROS can cause oxidation of proteins and DNA, inducing damage to nearby tissues.…”
Section: Discussionmentioning
confidence: 99%